Sekolah Perempuan Hebat Sebagai Upaya Memperkuat Ketahanan Ekonomi Keluarga Melalui Pemberdayaan Perempuan “Pengolahan Butternut Squash” - Muhammad Ibrahim; Rusmin Husain; Mohamad Zubaidi; Kartini Marzuki; Asep Saepudin (CERED Indonesia Publishing, 2025)
This great Women's school program provides education about gender equality and women's rights. Women's Schools cannot be separated from the process of individual or group self-development. Therefore, women must be empowered through the Women's School program. The women's school program to increase family economic resilience is an educational initiative specifically designed to provide knowledge, skills, and training on women's rights and economic opportunities. Improving women's skills in managing Butternut Squash to become a nutritious snack for children including mochi, crispy Butternut Squash, pumpkin dodol, and pumpkin jam, which was initiated through the Women's school program, Building partnerships based on family economic resilience with the village government, Social Service, Cooperative and MSME Service, the Family Hope Program Implementation Unit (UPPKH).